Metabolic dysfunction associated steatotic liver disease in patients with plaque psoriasis: a case–control study and serological comparison - Lin, Zheng; Shi, Yue-yi; Yu, Lu-yan; Ma, Chen-xi; Pan, Si-yi; Dou, Yuan; Zhou, Qiu-jun; Cao, Yi (Frontiers in Medicine, 2024)
Background: The relationship between plaque psoriasis and both MASLD and lean MASLD has not been sufficiently explored in the current literature. Method: This retrospective and observational study was carried out from January 2021 to January 2023 at The First Affiliated Hospital of Zhejiang Chinese Medical University. Patients diagnosed with plaque psoriasis and a control group consisting of individuals undergoing routine physical examinations were enrolled. The incidence of MASLD and lean MASLD among these groups was compared. Additionally, patients with plaque psoriasis were divided into those with MASLD, those with lean MASLD, and a control group with only psoriasis for a serological comparative analysis. Results: The incidence of MASLD in the observation group and the control group was 43.67% (69/158) and 22.15% (35/158), respectively (p<0.01). Furthermore, the incidence of lean MASLD within the observation group and the control group was 10.76% (17/158) and 4.43% (7/158), respectively (p<0.01). After controlling for potential confounding variables, plaque psoriasis was identified as an independent risk factor for MASLD with an odds ratio of 1.88 (95% cl: 1.10-3.21). In terms of serological comparison, compared to the simple psoriasis group, we observed a significant elevation in the tumor marker CYFRA21-1 levels in both groups compared to the control group with simple psoriasis (p<0.01). Moreover, the MASLD group exhibited elevated levels of inflammatory markers and psoriasis score, whereas these effects were mitigated in the lean MASLD group. Conclusions: The prevalence of MASLD and lean MASLD is higher among patients with psoriasis. Those suffering from psoriasis along with MASLD show increased psoriasis scores and inflammatory markers compared to those without metabolic disorders. MASLD likely worsens psoriasis conditions, indicating the necessity of targeted health education for affected individuals to reduce the risk of MASLD, this education should include guidelines on exercise and diet. In serological assessments, elevated levels of cytokeratin 19 fragment (CYFRA21-1) were noted in both MASLD and lean MASLD groups, implying a potential synergistic role between psoriasis and MASLD.